Coronavirus, the King Who Wanted More Than a Crown: From Common to the Highly Pathogenic SARS-CoV-2, Is the Key in the Accessory Genes? - Chazal, Nathalie (Frontiers in Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), that emerged in late 2019, is the etiologic agent of the current "coronavirus disease 2019" (COVID-19) pandemic, which has serious health implications and a significant global economic impact. Of the seven human coronaviruses, all of which have a zoonotic origin, the pandemic SARS-CoV-2, is the third emerging coronavirus, in the 21st century, highly pathogenic to the human population. Previous human coronavirus outbreaks (SARS-CoV-1 and MERS-CoV) have already provided several valuable information on some of the common molecular and cellular mechanisms of coronavirus infections as well as their origin. However, to meet the new challenge caused by the SARS-CoV-2, a detailed understanding of the biological specificities, as well as knowledge of the origin are crucial to provide information on viral pathogenicity, transmission and epidemiology, and to enable strategies for therapeutic interventions and drug discovery. Therefore, in this review, we summarize the current advances in SARS-CoV-2 knowledges, in light of pre-existing information of other recently emerging coronaviruses. We depict the specificity of the immune response of wild bats and discuss current knowledge of the genetic diversity of bat-hosted coronaviruses that promotes viral genome expansion (accessory gene acquisition). In addition, we describe the basic virology of coronaviruses with a special focus SARS-CoV-2. Finally, we highlight, in detail, the current knowledge of genes and accessory proteins which we postulate to be the major keys to promote virus adaptation to specific hosts (bat, human), to contribute to the suppression of immune responses, as well as to pathogenicity.